Pengaruh Penerapan Strategi Relating, Experiencing, Applying, Cooperating, Transferring (REACT) Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas XII IPS SMAN 2 Padang - TIA MARIADI (Departemen Matematika, 2019)
Mathematical communication skills are one of the goal of mathematics learning that must be achieved by students. But in the reality at SMAN 2 Padang this ability is still not optimal and do not facilitated yet for improving those skill well. One effort to overcome these problems is to apply the Relating, Experiencing, Applying, Cooperating, Transferring (REACT) strategies. This type of research is quasi-experimental and descriptive research design with Randomized Control Group Only Design. The authentication of the research hypotheses using t-test.Based on the results of data analysis, it was concluded that the mathematical communication skills of students who learn using the REACT strategies is better than the mathematical communication skills of students who learn by direct learning in class XII IPS SMAN 2 Padang. Keywords – Mathematical communication skill, REACT, Direct Learning